Deep Brain Stimulation for Essential Tremor: Targeting the Dentato‐Rubro‐Thalamic Tract?. Issue 2 (11th September 2014) - Schlaier, Juergen; Anthofer, Judith; Steib, Kathrin; Fellner, Claudia; Rothenfusser, Eva; Brawanski, Alexander; Lange, Max
<x xml:space="preserve">Abstract</x> Objective The aim of our study was to evaluate the influence of the stimulation site relative to the dentato‐rubro‐thalamic tract (DRTT) on the alleviation of tremor in deep brain stimulation. Methods Ten DRTTs in five patients were investigated using preoperative diffusion tensor imaging (DTI). Regions of interest for fiber tracking were located in the cerebellar dentate nucleus, the superior cerebellar peduncle and the contralateral red nucleus. The position and distance of all intraoperative stimulation sites to the DRTT were measured and correlated to the amount of tremor reduction. Results Nine of 10 DRTTs could be identified using DTI‐based fiber tracking. Better tremor reduction was achieved in locations in or posterior and lateral to the DRTT than in medial and anterior positions (p = 0.001). Stimulation sites inferior to and in the DRTT achieved better results than locations superior to the DRTT (p < 0.05). The vicinity of the stimulation site to the DRTT did not correlate with tremor alleviation. Discussion In deep brain stimulation targeting for thalamic stimulation sites is limited to statistical, atlas‐based coordinates. Diffusion tensor imaging and fiber tracking was used to visualize the dentato‐rubro‐thalamic tract as a potential, individualized target structure. However, we could not demonstrate that contacts closer to the DRTT provided better clinical effects than distant contacts, in any given direction. DTI sequences with a higher number of read‐out directions, probabilistic fiber tracking and three Tesla MRI scanners may lead to different results in the depiction of the chosen fiber tract and may provide a better correlation with stimulation effects. Conclusions The results do not provide sufficient evidence to define the DRTT as a new DBS‐target for tremor. Further investigations on different fiber tracts, DTI sequences, and fiber tracking algorithms are mandatory.